One Door, One Voice: Kalla Group's Crisis Communication Management for Corporate Reputation Protection - Ma'rifatun Qomariyah; Arianto; Muh. Akbar; Irnawati Bahtiar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2026)
The tragic death of a student at SMP Islam Athirah Makassar in 2023 became a moral crisis that shook the community, not only threatening the school's legitimacy but also damaging the reputation of Kalla Group as the parent company. This crisis, involving the loss of life, attracted significant public attention and created a significant emotional impact, requiring a swift and organised response to mitigate reputational damage. This study aims to analyse the application of crisis communication management strategies through the principles of ‘one door, one voice’ and minimal public interaction in managing attribution of responsibility and protecting corporate reputation. This study uses a qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews and participatory observation of two key informants in the Kalla Group's Corporate Communication and Sustainability Department and analysed using grounded theory-based thematic analysis. The main findings of this study include the escalation of communication governance to the holding level, narrative control to prevent the amplification of secondary crises, and the application of measured empathy and strategic silence in reputation recovery. The significance of these findings is that they enrich the literature on corporate crisis communication by introducing crisis communication as an organisational governance practice that involves narrative control, and provide practical implications for multi-unit organisations in dealing with high-reputation-risk humanitarian crises.